Improving Portland Cement Properties with Additives - Kasimova, Guzal; Mukimov, Khusan (International Journal of Psychosocial Rehabilitation, 2020)
One of the most perspective directions in the beginning of the XXI century in the field of building materials technology is creation of materials with essentially new characteristics approaching them to metal, ceramics and polymers. It is represented that this serious problem can be solved, involving complex modifiers of a special purpose with which use it will appear possible to receive and group of the special binders. These materials should be characterized also high strength by indicators at bend and a stretching, and also ultrahigh density and durability at compression.The development of construction production necessitates the creation of effective high-quality materials, the use of which is economically feasible and can reduce energy costs and the consumption of raw materials. Increasing the strength of cement stone in the manufacture of concrete for various purposes is an urgent task, the solution of which can significantly reduce the consumption of binder in concrete or increase its strength.As a result of long-term studies, it was found that it is possible to successfully solve the problem of increasing strength and improving the characteristics of Portland cement due to its mechanic and chemical processing. This technology includes the mechanic and chemical processing of Portland cement and its modification. This article presents the results of a study of the effect of mineral and chemical additives on cement strength.